DEVELOPMENT OF BIOLOGICAL ASSESSMENT BASED ON STUDENT CRITICAL THINKING SKILLS: a case study in eleventh grade at MAN 2 Palembang - Aseptianova Aseptianova; Sulton Nawawi; Resti Maya Astia (JURNAL PENA SAINS, 2020)
This study aims to determine the characteristics and feasibility of biology assessment based on critical thinking skills. This research is a research and development that adapts to the McIntire Miller development model. The sample used in the first trial was 80 students, and in the second trial were 76 students. Data collection techniques using questionnaire sheets, questionnaire sheets, interview sheets, test instruments in the form of essay questions of biology grade XI based on critical thinking from Facione with indicators: interpretation, analysis, evaluation, explanation, conclusions, and self-regulation. Techniques of data analysis using qualitative analysis and quantitative analysis. The results of this study were in the form of a biology assessment based on critical thinking skills in the form of essays in odd semester XI material and from the results of the 1st and 2nd trials totaling 24 items. The content validity of biology assessment based on critical thinking skills is qualified to very high. The construct validity the items are 28  questions valid (1st trial) with reliability value is 0.875. Furthermore, 24 questions are valid (2nd trial) with reliability value is 0.764. The results of the level of difficulty test are 0.332 (1st trial) and 0.537 (2nd Trial). The value of discriminating power is 1,541 (1st trial) and 2,021 (2nd trial). The data shows that the items can be used to measure students' critical thinking skills. We can involve the mental processes of pupils by the test based on critical thinking skills.